Multiple-field interstitial photodynamic therapy of subcutaneously transplanted cholangiocellular carcinoma RS-1 in rats - Tzerkovsky, D.A. (Experimental Oncology, 2017)
The aim of present study was to investigate an antitumor efficacy of multiple-field interstitial photodynamic therapy (iPDT) in vivo. Materials and Methods: The study was performed on 15 white random-bred rats with subcutaneously transplanted cholangiocellular carcinoma RS-1. Chlorine-based photosensitizer (PS) Ce6CPPPS was administered via single injection at a dose of 2.5 mg/kg into the animal’s caudal vein. Photoirradiation (PI) of tumors was carried out 3 h after PS administration using 7 optical fibers SMA-905 with diode laser with 660 ± 5 nm wavelength at exposure doses of 150 and 300 J/cm²with 0.21 W/cm²fluency rate. The total power density was 360 mW and treatment time was 12 and 24 min. Antitumor efficacy of iPDT was assessed by evaluation of necrosis areas and depth of necrosis in experimental tumors. Results: The results have shown that interstitial PI with multi-field low power density enhanced the antitumor effect of PDT in the RS-1 model. Necrosis areas in tumor tissues after PI with exposure doses 150 and 300 J/cm²24 h and 96 h after treatment were 83.78 ± 4.25 and 100% (p = 0.00074); 56.79 ± 3.24 and 95.46 ± 1.64% (p < 0.00001), respectively. Conclusion: An analysis of the literature data and the results obtained in this study evidence on high effectiveness of the method of multiple-field.